Discrimination in Recruitment against Czech Citizens with Hearing Impairment - Havlová, Jana (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
This work deals with discrimination in recruitment against people with hearing impairment. The work defines basic concepts of the discrimination, hearing impairment and the Czech sign language including the basic legislation on this issue. In this context, research has been carried out in order to identify attitudes and experience of people with hearing impairment and the reactions of employers to a hearing-impaired job seeker.

Niniejsze opracowanie dotyczy dyskryminacji w zakresie rekrutacji osób z wadami słuchu. W artykule zdefiniowano podstawowe pojęcia dotyczące dyskryminacji, upośledzenia słuchu oraz czeskiego języka migowego, w tym podstawowe akty prawne w tym zakresie. W tym kontekście przeprowadzono badania mające na celu określenie postaw i doświadczeń osób z wadami słuchu oraz reakcji pracodawców na poszukującego pracy z wadą słuchu.
Keywords: discrimination; recruitment; persons with hearing impairment; dyskryminacja; rekrutacja; osoby z wadami słuchu